À l’envers du Grand Blanc, le sens inuit du paysage - Fabienne Joliet (Projets de Paysage)
The magnetic poles have always fascinated people. Namely because of their whiteness the expanse of which is traversed by a few Eskimos in the Arctic... Contrary to the Antarctic, the Arctic is inhabited. These Canadian people, recently renamed the Inuit, are proud of their representations of the environment, territory, and landscape which are intimately linked to those of their society and its native culture. The perspective of Inuit from the Nunavik region was ignored by Westerners because these people were for a long time held apart from the colonial assimilation process. Theirs is an original Inuit point of view concerning territories which are not considered virgin and are not always white with snow.